2014
DOI: 10.1108/emjb-05-2013-0024
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of Islamic (participation) banks and commercial banks in Turkish banking sector

Abstract: Purpose – The purpose of this paper is to attempt to compare the performance of Islamic banks against conventional banks in Turkey. This comparison is much more distinctive and significant in Turkey when compared to other countries, as Turkey stands as a model for the world in interest-free banking system. Design/methodology/approach – The comparative performance analysis was conducted by means of logistic regression method during the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…Other studies have shown conflicting results on this matter. Saifullah (2010), Rozzani and Rahman (2013), Erol et al (2014), Hadriche (2015), and Khediri et al (2015) suggest that Islamic banks are more profitable; while that is not the case by studies done by Fayed (2012), and Wasiuzzaman and Gunasegavan (2013) Samad (2004) discussed the performance of Islamic banks and conventional banks in Bahrain after the first Gulf War in 1991. Comparative financial measure is expressed by using various financial ratios and they indicate that there is no significant difference in the profitability and liquidity between Islamic banks and conventional banks.…”
Section: Introductionmentioning
confidence: 91%
“…Other studies have shown conflicting results on this matter. Saifullah (2010), Rozzani and Rahman (2013), Erol et al (2014), Hadriche (2015), and Khediri et al (2015) suggest that Islamic banks are more profitable; while that is not the case by studies done by Fayed (2012), and Wasiuzzaman and Gunasegavan (2013) Samad (2004) discussed the performance of Islamic banks and conventional banks in Bahrain after the first Gulf War in 1991. Comparative financial measure is expressed by using various financial ratios and they indicate that there is no significant difference in the profitability and liquidity between Islamic banks and conventional banks.…”
Section: Introductionmentioning
confidence: 91%
“…The result shows that Islamic banks in Iran are more profitable than conventional banks in Turkey. In addition Erol et al (2014) investigates the comparison of the performance of Islamic banks and conventional banks in Turkey. The aims of this study to analyses the performance of the Islamic banks and conventional banks in Turkey in terms of Profitability and asset management.…”
Section: Profitabilitymentioning
confidence: 99%
“…Literature Review:- Erol et al (2014) conducted a study to compare the performance of the Islamic banks within Turkish context. Erol et al (2014) reported that Islamic banks are performing better than commercial banks.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Erol et al (2014) reported that Islamic banks are performing better than commercial banks. However, Riaz et al (2014) noted that Islamic banks have not fully adopted Islamic principles within Pakistani context.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%